Perencanaan Pengelolaan Sampah di Kecamatan Bekasi Utara - Ismi Elsaumitha; Mulyo Hartono; Joko Priono (DPPM Universitas Pelita Bangsa, 2022)
One of the current waste problems is waste generation. Population growth results increasing in various kinds of activitiy, therefore waste management is required. North Bekasi was a district located in Bekasi City, the population on 2021 is Â± 337,013 people. The purpose of this study is to evaluate the condition of waste management system and plan more effective and efficient waste management in the District of North Bekasi. The method used to project waste generation in the coming year is estimated according to population growth in 2011 2021 with the guidance of SNI No. SNI 19-2454-2002. Total waste generation in North Bekasi District in 2021 is 338,276,7988 m3/year and 60% transported. The plan is accumulated for the next 20 years by determining the process of collecting in 2 categories of organic and inorganic waste, transportation by trucks with a capacity of 20m2 with 9 trucks as much as 2 times in the village. So it takes a fee of Rp. 3.027.591965/year. Keywords: Waste, Plan, Manage, Storage, Waste Generation Projections